Youth perceptions of trade unions in malaysia: awareness, relevance, and barriers in the digital and gig economy era - Ismail, Fadillah; Zhe, Eric Chee Ming (Journal of Islamic, Social, Economics and Development, 2026)
Trade unions remain a central mechanism for protecting workers’ rights and sustaining industrial harmony, yet their relevance is increasingly questioned by younger workers in an employment landscape shaped by digitalisation and the gig economy. This paper synthesises key literature to explain how Malaysian youth perceive trade unions in terms of awareness, relevance, and barriers to engagement. It highlights a persistent decline in union participation and emphasises that limited knowledge of union roles and benefits is a primary driver of youth detachment, reinforcing perceptions that unions are outdated or misaligned with contemporary work arrangements. The discussion further shows that youth perceptions are shaped by broader influences, including family and workplace experiences, media narratives, and trust in union transparency and leadership. To strengthen youth engagement, the paper consolidates practical strategies centred on digital outreach and social media communication, early exposure through education-sector partnerships, flexible membership models for non-standard workers, and governance reforms that enhance transparency and youth representation.